PENGARUH PENAMBAHAN BAKTERI PROBIOTIK DAN SUMBER CARBON DALAM SISTEM BIOFLOK TERHADAP FCR IKAN NILA LARASATI (OREOCHROMIS SP.) - Titin Liana Febriyanti; Suminto Suminto; Sutrisno Anggoro (LPPM Universitas Muhammadiyah Gorontalo, 2018)
The high demand for fish consumption, especially freshwater fish, make cultivator developing aquaculture especially intensive systems, but constrained by various problems. Such as environmental pollution and increased cases of diseases. Then the need for such a solution that is like biofloc cultivation system. The purpose of this research is to know the combination of optimal biofloc system treatment for Tilapia fish (Oreochromis sp.) FCR (Feed Conversion Ratio). The experimental design used in this study was factorial design, with three repetitions. Factor 1 (ratio C: N), which consists of 3 levels C: N: 12, 18, and 24; Factor 2 (concentration of probiotic bacteria), which consists of two levels of 106 and 108 CFU / ml. This study consisted of six treatments namely A1B1 (ratio C: N 12 + bacterium 106 cfu / ml); A1B2 (ratio C: N 12 + bacterium 108 cfu / ml); A2B1 (ratio C: N 18 + bacteria 106 cfu / ml); A2B2 (ratio C: N 18 + bacteria 108 cfu / ml); A3B1 (ratio C: N 24 + bacteria 106 cfu / ml); A3B2 (ratio C: N 24 + bacteria 108 cfu / ml). The parameter observed is the FCR. The results of this study is the highest FCR on the C / N treatment Ratio 24 and at the density of probiotic bacteria 108 CFU / ml that is equal to 1.69